2020
DOI: 10.1016/j.cegh.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis, human immunodeficiency viruses and TB/HIV co-infection in pregnant women: A meta-analysis

Abstract: Background: Acquired Immunodeficiency Syndrome (AIDS) and tuberculosis (TB) represent major public health problems. The aim of this systematic review and meta-analysis is the assessment of the prevalence of tuberculosis, human immunodeficiency viruses (HIV), and co-infection of both, in pregnant women. Methods: We searched the literature in PubMed, Scopus, EMBASE, Web of Knowledge and MeSH, from all years of study until 25 April 2018, for articles and abstracts describing tuberculosis, HIV, and co-infection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The authors of this review have decades of experience in caring for pregnant people with TB in a myriad of settings on six continents. Some important topics in the management of pregnancy and TB were beyond the scope of this review, including management of comorbidities (i.e., HIV, diabetes mellitus) 14 16 and the care of infants/children with TB disease.…”
Section: Methodsmentioning
confidence: 99%
“…The authors of this review have decades of experience in caring for pregnant people with TB in a myriad of settings on six continents. Some important topics in the management of pregnancy and TB were beyond the scope of this review, including management of comorbidities (i.e., HIV, diabetes mellitus) 14 16 and the care of infants/children with TB disease.…”
Section: Methodsmentioning
confidence: 99%
“…HIV infection, the most powerful risk factor for active TB disease, increases latent TB reactivation 20-fold [ 23 ], and HIV co-infection triggers a substantial suppression of Mycobacterium TB-specific IFN-γ responses in a CD4+ T cell count-dependent manner, which suggests that the higher risk of active TB disease during pregnancy is due to failing to control the TB infection [ 24 ]. Pregnancy in HIV-positive women increases TB acquisition by 2.56-fold [ 4 ], and TB and HIV co-infection increases neonatal death 3-folds [ 25 ] together with vertical transmission of 15% for TB and 10% for HIV [ 26 ].…”
Section: Interaction Between Tb and Pregnancymentioning
confidence: 99%
“…About 90% of the cases are found in South-East Asia, Africa and the Western Pacific, with India, China, Indonesia, the Philippines and Pakistan as the worst-affected countries, and women accounted for one-third of all cases with higher prevalence in the reproductive ages [ 2 ]. Globally, 216 500 active TB cases were estimated in pregnant women in 2011 [ 3 ], the risk increased by 2.56-fold in pregnant women with HIV infection [ 4 ], the commonest co-infection among low- and middle-income countries where most maternal mortality cases occurred [ 5 ]. The COVID-19 pandemic led to an 18% fall in TB notifications in 2020 with India, Indonesia, and the Philippines accounting for 93% of the drop, disruption of TB and HIV services resulted in resurgence in TB-related mortality [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported strong associations of some pathogens such as human cytomegalovirus (HCMV), viremia (95), malaria (96), and tuberculosis (97) with the in utero transmission of HIV-1, thereby contributing to the high incidence of MTCT. Maternal placenta HCMV infection facilitates inflammation, chronic villitis, and trophoblast damage, providing potential HIV-1 access into the primary receptor (CD4) and coreceptor (CCR5) target cells (95).…”
Section: Prevention Of Mtct Of Hivmentioning
confidence: 99%
“…There is a dearth of information on the effect of standard RUTF on mortality, especially in the context of HIVinfected infants (97). It is, therefore, important to assess the effectiveness and cost analysis of formulations of ready-touse foods for the nutritional management of SAM in HIVinfected infants and children using properly designed RCTs with standardized outcome measures that include diarrhea and other complications.…”
Section: Dietary Formulations For Feeding Severely Malnourished Infantsmentioning
confidence: 99%